KOLONISASI BAKTERI ENDOFIT PADA AKAR TUMBUHAN ANDALEH (Morus macroura Miq.) - Sisri Yandila; Dwi Hilda Putri; Mades Fifendy (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2018)
Endophytic bacteria are bacteria living in plant tissues and symbiotic mutualism with their host. The excess production of bioactive substances from endophytic microorganisms among others, microorganisms are easy to grow, have shorter life cycles than plants and can produce large amounts of bioactive compounds. Endophytic bacteria found in plants generally originate from the roots and then spread through xylem tissue. Endophytic bacteria that live within the plant tissue for a certain period and are able to live by forming colonies in plant tissue without harming the host. Endophytic bacteria can be isolated from sterile plant tissue surfaces or extracted from inner plant tissue. The purpose of this study was to determine the type of bacterial isolate of edofit found in the root of Andaleh plant. The method used to isolate endophytic bacteria from the root plant Andaleh is streak plate method. Identification of bacteria macroscopically and microscopically. The results obtained were 16 isolates of endophytic bacteria from the roots of Andaleh plant seen from different colony forms. Identify microscopically with Gram staining